Photocatalytic, nitrite sensing and antibacterial studies of facile bio-synthesized nickel oxide nanoparticles - Kumar, C.R. Rajith (H. : ĐHQGHN, 2020)
In the present work, Nickel oxide nanoparticles (NiO NPs) were synthesized using leaves extract of C. gigantea through a solution combustion method. The NiO NPs were characterized through analytical techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Fourier transform infrared spectroscopy (FT-IR). The XRD results revealed rhombohedral structured crystallites with average size of 31 nm. SEM and TEM images indicate that the nanoparticles are agglomerated with an asymmetrical shape. The optical energy bandgap of 3.45 eV was estimated using UV-diffused reflectance spectroscopy (UV-DRS). The synthesized NiO NPs have shown superior photodegradation for methylene blue (MB) dye. Further, the antibacterial activity of the prepared nanoparticles was tested against E.coli and S.aureus bacterial strains. In addition, nanoparticles were utilized for electroanalytical applicability as a novel non-enzymatic sensor in the trace level quantification of nitrite. The proposed nitrite sensor showed wide linearity in the range 8e1700 mM and good stability with a lower detection limit of 1.2 mM.